Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10661-007-0076-6
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air monitoring of Beijing MSW logistics facilities in 2006

Abstract: In China, "green" integrated waste management methods are being implemented in response to environmental concerns. We measured the air quality at several municipal solid waste (MSW) sites to provide information for the incorporation of logistics facilities within the current integrated waste management system. We monitored ambient air quality at eight MSW collecting stations, five transfer stations, one composting plant, and five disposal sites in Beijing during April 2006. Composite air samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…14 Li et al reported that the concentration of H 2 S in the air around a land ll in Beijing was less than 36 ppb. 15 The concentration of H 2 S in the ambient air of land lls in Korea, Spain, and the US is in the ppb level. 16-18 H 2 S pollution levels were relatively low in the base before garbage classi cation.…”
Section: Resultsmentioning
confidence: 99%
“…14 Li et al reported that the concentration of H 2 S in the air around a land ll in Beijing was less than 36 ppb. 15 The concentration of H 2 S in the ambient air of land lls in Korea, Spain, and the US is in the ppb level. 16-18 H 2 S pollution levels were relatively low in the base before garbage classi cation.…”
Section: Resultsmentioning
confidence: 99%